MOTIVASI MASYARAKAT KOTA JAYAPURA DALAM AKTIVITAS OLAHRAGA PADA MASA PANDEMI COVID-19 - Ince Abdul Muhaemin (UNIVERSITAS NEGERI MAKASSSAR, 2022)
The purpose of this research is to find out how much motivation the people of Jayapura city are in sports activities during the COVID-19 pandemic. This type of research is descriptive quantitative research with survey techniques using questionnaires. The population in this study was the people of the city of Jayapura who carried out sports activities during the COVID-19 pandemic, while the sample of this study was 100 people obtained using the sampling formula from Issac and Michael. The results of this study showed that the motivation of the people of Jayapura City in sports activities during the COVID-19 pandemic in terms of the physiological needs aspect obtained a percentage of 87% with a very high category, the aspect of security needs obtained a percentage of 88% with a very high category, aspects of social needs obtained a percentage of 78% in the high category, the aspect of the need for appreciation obtained a percentage of 79% in the high category, the aspect of the need for self-actualization obtained a percentage of 80% in the high category. Based on the results of the interpretation of the research data from the five indicators, it can be seen that the level of motivation of the people of the city of Jayapura in sports activities during the COVID-19 pandemic is 82.4% which is categorized as very high.